Authentic Leadership, Traditionality, and Interactional Justice in the Chinese Context. (July 2014) - Li, Fangjun; Yu, Kuo Frank; Yang, Jixia; Qi, Zhenjiang; Fu, Jeanne Ho-ying
Abstract: We examine the effects of authentic leadership on subordinates in the Chinese context. Drawing on attribution processes of self-disclosure, we propose that authentic leaders engaging in self-disclosure practices cultivate subordinates' positive feelings that their leaders like and trust them. We further explain how and why authentic leadership particularly influences highly traditional Chinese subordinates. We propose that Chinese traditionality strengthens the positive effects of authentic leadership on subordinates' perceptions that their leader practices interactional justice, which in turn positively relates to their in-role performance, creativity, and organizational citizenship behaviour. In Study 1, we surveyed 199 employees in 47 work units from nine high-technology organizations in China. The results support the hypothesized relationships. In Study 2, we surveyed 170 employees in 46 work units from various organizations in China. The results show that authentic leadership effects remain unchanged after controlling for the effects of transformational leadership. We discuss the implications for leadership effectiveness in the Chinese context.